The role of maternal nutrition on oocyte Size and quality, with respect to early larval development in the coral-eating Starfish, Acanthaster planci (2016)
ABSTRACT: Variation in local environmental conditions can have pronounced effects on the population structure and dynamics of marine organisms. Previous studies on crown-of-thorns starfish, Acanthaster planci, have primarily focused on effects of water quality and nutrient availability on larval growth and survival, while the role of maternal nutrition on reproduction and larval development has been overlooked. To examine the effects of maternal nutrition on oocyte size and early larval development in A. planci, we pre-conditioned females for 60 days on alternative diets of preferred coral prey (Acropora abrotanoides) versus non-preferred coral prey (Porites rus) and compared resulting gametes and progeny to those produced by females that were starved over the same period. Females fed ad libitum with Acropora increased in weight, produced heavier gonads and produced larger oocytes compared to Porites-fed and starved females. Fed starfish (regardless of whether it was Acropora or Porites) produced bigger larvae with larger stomachs and had a higher frequency of normal larvae that reached the late bipinnaria / early brachiolaria stage compared to starved starfish. Females on Acropora diet also produced a higher proportion of larvae that progressed to more advanced stages faster compared to Porites-fed starfish, which progressed faster than starved starfish. These results suggest that maternal provisioning can have important consequences for the quality and quantity of progeny. Because food quality (coral community structure) and quantity (coral abundance) varies widely among reef locations and habitats, local variation in maternal nutrition of A. planci is likely to moderate reproductive success and may explain temporal and spatial fluctuations in abundance of this species.